Study on Improving West Africa’s Coastal Security Management: An Analytical Model - Chinedum Onyemechi; Abiodun Sule; Kenneth U. Nnadi (International Research in Environment, Geography and Earth Science Vol. 8, 2021)
Maritime security strategies adopted by the navy and coastguards were reviewed in the work with a view to determining spatial coverage of acquired maritime domain in the new legal regime of the exclusive economic zone. Variables applied in the assessment include the coastal resources of the state such as renewable resources like fishes and non renewable under water resources such as oil. Others include the freedom sectors such as marine traffic, pipelines, underwater cables and air traffic. In the course of the research, regression analytical tools were applied to ascertain the quality of security. Recommendations for improvement on the quality of security were then made for the region based on research output. The concepts of sea base and the sea shield concepts were reviewed as a security strategy in Nigeria’s maritime domain. Analyses of reported maritime security problems in the region were made considering the two frameworks of sea shield and sea bases. Further recommendations were then made to the advantage of the entire system. A re-engineering of the present logistics operations methodology was suggested for world’s most advanced nations involved in anti-piracy activities in the world’s maritime domains. Superiority of the security outfits of nations involved in anti-piracy activities was emphasized. A joint sea and air logistics combination was deemed to produce superior maritime effects.